Cysterskie szkoły w Szczyrzycu od 1780 roku do lat trzydziestych XX wieku - Marszalska, Jolanta M. (Biuletyn Historii Wychowania, 2013)
The goal of this article is to present a school operating as part of the Cistercian abbey in Szczyrzyc. In the 18th century, some Cistercian abbeys assumed the responsibility of establishing and managing elementary schools. It was also the case in Poland provided that the legislation of the respective empire (Russia, Prussia or Austria) allowed for such arrangements. The abbey in Szczyrzyc was in charge of the school facilities and competent teachers. While some of them were the local monks, a respective state authority supervised adherence to the curriculum. The first existing source of information about the school at the Cistercian abbey in Szczyrzyc comes from 1780. Despite numerous obstacles related to the political situation in the partitioned Poland, the abbey educated the local children continuously albeit more or less successfully until the middle of the 20th century, involving the monks in the education process. Keywords: education, cistercians, Szczyrzyc, religious school